Review of the wolf spider genus Halocosa Azarkina & Trilikauskas, 2019 from China (Araneae, Lycosidae) - Lu-Yu Wang; Muhammad Irfan; Yuri M. Marusik; Zhi-Sheng Zhang (ZooKeys)
The wolf spider genus Halocosa Azarkina & Trilikauskas, 2019 from China is reviewed, including two species: H. cereipes (L. Koch, 1878) (♂♀) and H. hatanensis (Urita, Tang & Song, 1993) (♂♀). Both species are restricted to northern China, with H. cereipes recorded from China for the first time. Halocosa jartica (Urita, Tang & Song, 1993), syn. nov. is synonymized with H. hatanensis (Urita, Tang & Song, 1993). Detailed species descriptions, along with morphological photos, genitalia illustrations, SEM photos of the bulbs and photos of live specimens are also presented.